Feeding and developmental outcomes after neonatal seizures—A prospective observational study - Katelyn H. Roberts; John D. E. Barks; Hannah C. Glass; Janet S. Soul; Taeun Chang; Courtney J. Wusthoff; Catherine J. Chu; Shavonne L. Massey; Nicholas S. Abend; Monica E. Lemmon; Cameron Thomas; Ronnie Guillet; et al. (Annals of the Child Neurology Society, 2023)
Abstract Objective Among neonates with acute symptomatic seizures, we evaluated whether the inability to take full feeds at the time of hospital discharge from neonatal seizure admission is associated with worse neurodevelopmental outcomes, after adjusting for relevant clinical variables. Methods This prospective, nine‐center study of the Neonatal Seizure Registry (NSR) assessed characteristics of infants with seizures, including evidence of brainstem injury on magnetic resonance imaging (MRI), mode of feeding upon discharge, and developmental outcomes at 12, 18, and 24 months. The inability to take oral feeds was identified through a review of medical records. Brainstem injury was identified through a central review of neonatal MRIs. Developmental outcomes were assessed with the Warner Initial Developmental Evaluation of Adaptive and Functional Skills (WIDEA‐FS) at 12, 18, and 24 months corrected age. Results Among 276 infants, inability to achieve full oral feeds was associated with lower total WIDEA‐FS scores (160.2 ± 25.5 for full oral feeds vs. 121.8 ± 42.9 for some/no oral feeds at 24 months, p < 0.001). At 12 months, a gastrostomy tube was required for 23 of the 49 (47%) infants who did not achieve full oral feeds, compared with 2 of the 221 (1%) who took full feeds at discharge (p < 0.001). Conclusions The inability to take full oral feeds upon hospital discharge is an objective clinical sign that can identify infants with acute symptomatic neonatal seizures who are at high risk for impaired development at 24 months.